PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN SIKAP TOLERANSI KERAGAMAN SUKU BANGSA DAN BUDAYA KELAS V - Aji Fauziana Ridwan; Seli Marlia; Asep Priatna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2018)
This study is based on the problems found in the fifth grade of SD Negeri Rahayu, namely: (1) students' tolerance is still low; (2) the social studies learning process still takes place in a classical manner (Teacher Center); and (3) lack of utilization of learning models / methods. Thus the purpose of this study are: (1) to describe how the activities of students in learning the tolerance attitude of ethnic diversity and culture by applying the method of role playing; and (2) to describe an increase in the ability of tolerance of class V students by applying the role playing method in learning. The research method used is Classroom Action Research (CAR) with the design of the Kemmis and MC models. Taggart is carried out for two cycles starting from the stages of planning, implementation, observation, and reflection. The subjects in this study were class V SD Negeri Rahayu 2018/2019 academic year, totaling 28 students. The instruments used to collect data in this study are: (1) observation sheet; and (2) questionnaire. The results of the study showed that: (1) in general the activities of fifth grade students in learning Social Sciences regarding the tolerance attitude of ethnic and cultural diversity experienced positive development. This is based on the average activity of students in the first cycle, which is 56% and in the second cycle increases to 90%; and (2) in general the increase in tolerance of ethnic groups and the culture of class V students by using the role playing method in learning Social Sciences experienced positive development. This is based on N-Gain data in cycle I, o, 38 and in cycle II it increases to 0.58. The percentage completeness data obtained in the first cycle is 86%, after reflecting and following up on cycle II it increases very well to 100%.